Pengembangan Praktikum Fisika Materi Hukum Kekekalan Momentum Menggunakan Aplikasi Video Tracker - Khotijah Khotijah; Arsini Arsini; Sheilla Rully Anggita (Faculty of Science and Education, UIN Walisongo Semarang, 2019)
This study aims to determine the feasibility and the effectiveness of using a video tracker application for practicum of physics 1 on momentum conservation. This is included in research and development type. Stages carried out in this study include: 1) define, is done by giving questionnaires and interviews, 2) design, includes media selection, format selection and produce the initial product design, 3) development, includes product development and material expert validation assessment, media experts and linguists and limited field testing. The validation test results obtained that the media is feasible to use with a percentage of 88% based on material experts with very good categories, 85% based on media experts with very good categories, and 78% based on linguists with good categories. The effectiveness of media is shown by high average value of the experimental class of 84,06 compared to the control class of 70,97. Student responses to the use of products are categorized very well with a percentage of 89%.